Determinación de pruebas laboratoriales como ayuda diagnóstica de anemia ferropénica y sus factores de riesgo en mujeres gestantes, que acuden al Área de Gineco-Obstetricia del Hospital Provincial General Isidro Ayora de Loja. - Espinosa Jimenez, Flavio Arturo (2013)
Anemia is acommonclinical conditionduring pregnancywhereiron deficiencyis themost popularnutritional failure. Its prevalenceis highin pregnant womenwhich increasesthe risksof developing diseasesmaternaland /or fetal. Which is whyit is consideredimportant to conductclinical laboratorytestsduring pregnancyand post-gestational. The present studyaimed to:determinevalues​​ofRBC, Hematocrit, Hemoglobin, SerumIron, FerritinandTransferrinin pregnant womenfor identification ofiron deficiency anemiaandquantify the frequencyof iron deficiency anemiabygestationalcycle, and know therisk factorsindicativeiron deficiency anemiathrough asurvey, for which was conceived as atype ofdescriptive study, cross-sectional, which included 53pregnant women whomet theinclusion criteria andthe techniquewasperformedonautomated equipmentelectroquimiluminicenciaC 311COBAS, COBASE 411, andSysmex2000impedanceelectricalequipmentandflow cytometry. once theinvestigationconcludes that there isthe presence ofdecreased values​​ofred blood cells,hematocrit, hemoglobin, serum iron and ferritin, while regardingtransferrinlevels are elevated, the same thatleads to apresumptive diagnosisofiron deficiency anemia,the samethatis more prevalentduring the thirdmonth of pregnancy, thisproblem becomes moreevident dueto the low consumptionof foods withironinthe study population Keywords: Iron-DeficiencyAnemia, redblood cells, hematocrit, hemoglobin, serumiron, transferrinandferritin.